Design of Close Circuit Television Video System for Subway Train - LIU Peng-xiang; LIU Dong-liang; REN San-gang; HUANG Wen-jing (机车电传动)
Design, transmission style and system functions of close circuit television video system in subway train were described, which was used for the accident prevention and analysis, and provided technical support for emergencies treatment in subway operation.